Mate II - Limites
Mate II - Limites
Mate II - Limites
URBANISMO
LIMITES
ESTUDIANTE:
EFFIO HUAMANCHUMO YESSENIA
PROFESORA:
DELGADO NAMUCHE, KATTY ADELAIDA
SECCION:
C
CICLO:
III
Pimentel – 2020
I. Aplicando la definición de limite, demostrar los
siguientes límites:
2° | 3x+5 | k>0
3° | x-2 | < ƍ, = 1
-1 < x-2< 1
1 < x< 3
3 <3x< 9
8 <3x+5< 14
| 3x+15 | < 14
4° | x-2| < ƍ
| 3x+5 | < 14
| x-2 | | 3x+5 | < 14ƍ = ε
→ ε= 14 ƍ
ε
→ƍ= 14
ε
→ ƍ= min {1; 14 }
4
b) lim
x−2
=4
x→3
|12−4 x
X−2 | < ε
|−4X(x−3)
−2 |
<ε
¿
4 ¿ x−3∨ ¿ x−2∨¿ ¿ ¿ < ε
1
2° x−2 k<0
1 1
3° |x-3| < ƍ, = 2 (3-2)= 2
1
|x-3| < 2
1 1
- 2
< x−3<
2
5 7
<x<
2 2
1 3
< x−2<
2 2
2 1
< <2
3 x−2
| x−21 |<2
4° |x-3| < ƍ
| x−21 |<2
|x −3|2
4 =8 ƍ
|x−2|
5° ε= 8ε
ε
→ ƍ= 8
6° ƍ = min {12 ; 8ε }
c) lim √ 6−x=1
x→5
1° |√ 6−x−1|< ε
( √ 6−x −1 )∗( √ 6−x+1 )
| ( √ 6−x+1 ) |
6−x −1 |5−x|
| = |
√ 6−x−1 √ 6−x−1
1
2° √6−x +1 k<0
3° |5-x| < ƍ, = 1
-1 < 5-x < 1
-6 < -x < -4
0 < 6-x < 2
0 < √ 6−x< √2
1 < √ 6−x+1< √2+1
1 1
< <1
√ 2+1 √6−x +1
1
|√ 6−x +1 |
<1
4° |5-x| < ƍ
1
<1
√ 6−x +1
|5−x| ƍ
< =ε
√ 6−x +1 1
→ƍ=ε
5° ƍ= min {1; ε}
x 3−15 x−4
d) lim x−3
=0
x→4
x 3−15 x−4
Ұ ε > 0, Ǝ ƍ > 0 / 0 < |x-4| < ƍ → | x−3 |<ε
x 3−15 x−4
1°| x−3
<ε|
( x−4 ) ( x2 + 4 x+ 1 )
| ( x−3 ) | <ε
. cuadrado perfecto
x 2+ 4 x +1+3−3
x 2+ 4 x +4−3
( x +2 )2−3
|x−4||( x +2 )2−3|
<ε
|x−3|
2° |( x +2 )2−3|< k
1
<k
x−3
1 1
3° |x-4| < ƍ, = 2
( 4−3 )=
2
1
|x-4| < 2
−1 1
< x−4<
2 2
7 9
< x<
2 2
11 13
< x+2<
2 2
121 2 169
< ( x +2 ) <
4 4
109 157
< ( x +2 )2−3<
4 4
|( x +2 )2−3|< 157
4
1 1
4° |x−4|< ƍ ,= 2 ( 4−3 )= 2
1
|x−4|<
2
−1 1
< x−4<
2 2
7 9
< x<
2 2
1 3
< x−3<
2 2
2 1
< <2
3 x−3
| x−31 |<2
5° |x−4|< ƍ
|( x +2 )2−3|< 157
4
| x−31 |<2
|x−4||( x +2 )2−3| 2∗157
<ƍ
|x−3| 4
157
ƍ 2
=ε
2
ƍ ¿ 157 ε
2 x 2+2 x−12
a) lim
x →2 3 x 2−5 x−2
(2 x +6)( x−2)
lim
x →2 (3 x+1)( x−2)
(2 x +6)
lim
x →2 3 x+1
2 ( 2 ) +6 10
=
3 (2 )+7 7
b) lim √3 x 2+ 6−3
x →3 x−3
3
( √3 x2 +6 ) −33 ( 3 2
= √ x +6 x−3 ) ¿ ¿
x−3
x 2+ 6 x−27
lim ¿
x →3 ( x−3 ) ¿ ¿
( x +9 ) ( x−3 )
lim ¿
x →3 ( x−3 ) ¿ ¿
( x +9 )
lim ¿
x →3 ¿¿
3+ 9 12 4
= =
9+9+ 9 27 9
√3 1+ y−1 =¿ ¿
c) y →0 1− √1+ y
lim
3
( √3 1+ y) −13
lim 3
y →0 (1−√ 1+ y)( √ (1+ y)2 + √3 1+ y +1)
y
3
∗(1+ √1+ y )
(1−√ 1+ y )( √(1+ y )2+ √3 1+ y +1)
lim
y →0 (1+ √ 1+ y)
y (1+ √ 1+ y )
lim 3 3
y →0 − y ( √(1+ y)2 + √ 1+ y +1)
1+ √ 1+ y
−lim 3
y→0 ( √ (1+ y )2 + √3 1+ y +1 )
−1+1 −2
=
1+ 1+1 3
d) lim √3 7+ x 3−√ 3+ x 2
x →1 x−1
6 6
( √3 7+ x 3 ) −( √ 3+ x 2 ) (7+ x 3 )3−( 3+ x 2)3
lim =
x →1 ( x−1 )∗k ( x−1 )∗k
2 3
( 7+ x 3 ) − ( 3+ x 2 )
2 2 3
72 +2 ( 7 ) ( x 3 )+ ( x 3 ) −[ 33 +3 ( 3 )2 ( x 2) + 3 ( 3 ) ( x 2 ) + ( x 2 ) ]
49+ 14 x 3+ x 6 −27−27 x 2−9 x 4 −x 6
−9 x 4 +14 x 3−27 x 2 +22
−9 x 4 +14 x3 −27 x2 +22
lim
x →1 ( x−1 )∗k
−9 x 4 +14 x 3−27 x 2 +0 x+ 22
-9 14 -27 0 22
METODO DE RUFFINI
1 -9 5 -22 -22
-9 5 -22 -22 0
−9 x 3 +5 x2 −22 x−22
lim
x →1 ( x−1 )∗k
−9 x 3+ 5 x 2−22 x−22
lim 5 4 3 2 2 3 4 5
x →1 ( √3 7+ x 3 ) + ( √3 7 + x3 ) ( √ 3+ x 2 ) + ( √3 7+ x 3 ) ( √ 3+ x 2 ) + ¿ ( √3 7+ x 3 ) ( √3+ x2 ) + ( √3 7 + x 3) ( √3+ x2 ) + ( √ 3+ x 2 )
−9+5−22−22 −48 −1
= =
6∗25 6∗32 4